Association between Psychological Stress and Neck Pain among College Students during the Coronavirus Disease of 2019 Pandemic: A Questionnaire-Based Cross-Sectional Study - Amira Daher (MDPI AG, 2021)
The coronavirus disease of 2019 (COVID-19) greatly affected people’s lifestyles. We used an online, cross-sectional survey during a COVID-19-related lockdown in Israel, with the aim of investigating the effects of such lockdowns on students’ self-perceived stress and neck pain (NP). College students (N = 295) completed questions on sociodemographic characteristics, the Neck Disability Index (NDI), the Perceived Stress Scale, the Visual Analogue Scale (VAS), and NP frequency (four-point scale). Logistic regression models were calculated with the NDI as the dependent variable. In total, 35.6% of students experienced at least moderate NP-related disability (NDI ≥ 15), more during than before the lockdown. NP increased gradually, from a lifetime mean of 1.80 to a lockdown mean of 3.07 (χ2 = 316.72; p < 0.001). Students’ self-perceived stress was moderate, and 59.3% reported experiencing study-related stress. Higher levels of self-perceived stress, study-related stress, sitting >3 h/day, and a higher VAS score were associated with a higher risk of an NDI ≥ 15 (Nagelkerke’s R2 = 0.513, p < 0.001). The transition from on-campus to online learning seems to have exacerbated students’ NP, which was correlated to their study stress and lifestyles. These findings advocate for the need to promote the physical and mental health of students via e.g., mental health services and occupational and ergonomic consulting services.